Postdegree intentions of female international undergraduate students studying in Malaysia: A qualitative study - Kelly, A.; Bennett, Dawn; Giridharan, Beena; Rosenwax, L. (2020)
Higher education has been positively linked with increased opportunity for women, including enhanced employability, increased migration, enriched cultural capital, and improved language skills. With the number of international students rising, understanding postdegree intentions is increasingly important for institutions, policy makers, and administrators. This qualitative study explored the postdegree intentions of female international undergraduate students at the Malaysian campus of an Australian university. In-depth interviews were conducted with students from a range of degree programs and data was studied using thematic analysis. Findings revealed that postdegree intentions were substantially influenced by other people and policies; a common aspiration was to balance career and family; postdegree intentions were not solely career-focused; and the students anticipated discrimination and inequality but were determined to successfully navigate these.